The First Year and the Rest of Your Life : Movement, Development, and Psychotherapeutic Change. - Frank, Ruella (Taylor & Francis, 2010)
The movement repertoire that develops in the first year of life is a language in itself and conveys desires, intentions, and emotions. This early life in motion serves as the roots of ongoing nonverbal interaction and later verbal expression - in short, this language remains a key element in communication throughout life. In their path-breaking book, gestalt therapist Ruella Frank and psychoanalyst Frances La Barre give readers the tools to see and understand the logic of this nonverbal realm. They demonstrate how observations of fundamental movement interactions between babies and parents cue.